A small open economy before and during the crisis: the importance of banks, asset markets and monetary policy - Soares, Carla Sofia Caeiro (2020)
It is widely accepted that there are welfare bene ts from financial integration via risk sharing of idiosyncratic shocks. However, evidence suggests that aggregate shocks are preponderant in explaining business cycles, at least in the US and the euro area. This thesis discusses this idea, both theoretically and empirically, in the background of the euro area before and after the Great Recession. There are welfare gains for a SOE of financial integration, even when faced with aggregate shocks. A sudden stop scenario is thus more relevant for this SOE, but can be counteracted with monetary policy intervention in the affected markets.